INCREASING SALES WITH THE ROLES OF MARKETING MIX (A STUDY OF THE COSMETICS BUSINESS) - Nur Muftiyanto1, R.Taufiq; Hastuti, Indra (LPPM Universitas Duta Bangsa Surakarta, 2023)
Marketing mix is one method of winning an edge that makes sense for both organizations producing labor and products. The advertising mix is intended to determine the direction, the purpose of promotional options in the business related to market division, the idea of the target market, and the components of the marketing mix. Sometimes business in cosmetics tends to continue to grow. The growing interest in beautifying themselves has become a basic human need, having an impact on increasing the supply of cosmetic products. In the promotional role, the most difficult condition is to restrain the buyer from continuing to use the goods of the merchant, or it is often alluded to as client devotion. To ensure customer constancy, business people must have the right marketing procedures in promoting their products. One type of marketing techniques is a marketing mix system that combines products, prices, promotions, and places. If buyers are satisfied with the goods sold, they will be loyal. Assuming the reliability of the client is understood, it will affect the expansion of the deal.